Persepsi Penggunaan Bahasa Siswa SD Kelas 3 Secara Auditif - Al Gadri, Henri Henriyan (Jurnal Artikula, 2021)
This study discusses the auditive perception of the language use of 3rd grade elementary school students. MLU is a measure for children's syntactic development. Children's language acquisition involves two skills, namely the ability to produce speech spontaneously and the ability to understand the speech of others. The purpose of this research is to find out the perception of using the language of 10 year old 3rd grade elementary school students in an auditive way. Mean Length Of Utterance (MLU) is the theory used in this study. The method used in this research is descriptive content analysis. The method of data collection is done by observing the subject. This is done by recording all the children's speech, both visually and auditory. The MLU calculation is obtained from taking a speech sample of 100 utterances. Data analysis can be carried out in four steps, namely transcription of children's voice recording data, selection of children's regional language recording data, classification of recorded data based on the number of morphemes, exposure of the results of speech classification data analysis based on the number of morphemes. The result of this research is the MLU index is 1.76. Adapted to the stages proposed by Brown, the 10-year-old Alifa language development phase is in stage one